From LIKE/LOVE to habitual: the case of Mainland East and Southeast Asian languages - Fang Hongmei (Linguistics)
This paper documents the common grammaticalization path of the LIKE/LOVE constructions into expressing habitual aspect in Mainland East and Southeast Asian languages. The stages and degrees of grammaticalization for the LIKE/LOVE constructions vary cross-linguistically and different stages of evolution co-exist in one and the same language. Based on the synchronic data from a sample of six national languages in that region, it is found that the grammaticalization process in Chinese, Thai, and Lao is advanced while the process in Vietnamese, Khmer, and Burmese is incipient. At the initial stage of their grammaticalization, there are three context-induced intermediate steps of development before the constructions in question are compatible with inanimate subject referents and the habitual meaning becomes the only possible interpretation. At the later stage, languages vary in their combinability with stative verbs and in their possibility of occurring in future temporal context. The common human experience that if one likes/loves doing something, one tends to do it frequently renders it highly unlikely that this grammaticalization pattern is an areal feature confined to Mainland East and Southeast Asia.